A Study on the Works of Rohinton Mistry as a Weapon: Examining the Portrayal of Political Imbalances and Sufferings in Rohinton Mistry's Works (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The aim of this thesis is to discuss the intense streaks of political imbalances and sufferings of the common people as discerned in Rohinton Mistry’s works. The objective of this thesis includes a detailed and analytical study of the selected works. Every human life is beset with so many problems and sufferings at different levels. It is impossible for any human beings to exist without facing problems or sufferings in the world. It is due to ignorance, people are entangled in various disturbances from birth to the last breath. It is true that people have to face problems throughout their life and there is no way to avoid them. Rohinton Mistry’s works seem to be found that an author carry a mirror for the dusty highways of Indian society. Hence, the author shows the characters of poor people as a life of their own. Rohinton Mistry satirises vehemently the exploitations of the powerful people over the poor and downtrodden. Rohinton Mistry uses his works as a weapon against the exploiters. It has a deeper insight of political, nativity, and struggles such as ‘a slice of life’ of Indians and ‘picturesque’ of suffering people.